Factors influencing guest’s choices towards smoke free hotel / Nazmin Masngut and Nor Syahira Zainal Abidin - Masngut, Nazmin; Zainal Abidin, Nor Syahira (2019)
This research is a study about factors influencing guest’s choices towards smoking free hotel. Smoking is habit-forming and physically addictive, and causes premature illness and death due to lung cancer, cardiovascular disease and a host of other ailments, as well as reducing lung function and complicating other diseases such as asthma and tuberculosis. While smoking free is a place where people are not allowed to smoke. In this context, smoking free hotel room is a hotel that are prohibited to smoke in the room. The purpose of this study are to identify the factors influencing guest’s choices on smoking free hotel. To carry out this study, argumentative method was used. Data collected included the factors influence guest choices towards smoking free hotel. Results and findings from this study is health as the major factor influence guest’s choices towards smoking hotel room. While smell and health as the factors that influence guest’s choices towards smoking hotel room.